Molecular basis of whey protein functionality - Zoran Herceg; Anet Režek; Suzana Rimac Brnčić (Mljekarstvo)
Whey proteins constitute 18-20% of total milk protein content. Their nutritive value, accompanied by diverse physico-chemical and functional properties, make whey proteins widely applicable in food industry. Highly risen demands of consumers for tastier, healthier, suitable and more natural food products have given dairy industry the opportunity for development and enrichment of food products with whey protein supplements in order to increase their functional and nutritive properties. Development of these supplements mainly depended on recognition of the importance in understanding molecular basis of whey protein functionality from food scientists. Thereby, the aim of this paper is to expose the basis of whey protein functionality at one place, as the important supplement for food products.